Comparison of delay discounting of different outcomes in cigarette smokers, smokeless tobacco users, e-cigarette users, and non-tobacco users - DeHart, William Brady (J Exp Anal Behav, 2020)
Delay discounting is the process by which a commodity loses value as the delay to its receipt increases. Rapid discounting predicts various maladaptive behaviors including tobacco use. Typically, delay discounting of different outcomes has been compared between cigarette smokers and nonsmokers. To better understand the relationship of delay discounting to different modes of tobacco use, we examined the differences in delay discounting of different outcomes between cigarette smokers, smokeless tobacco users, e-cigarette users, and non-tobacco users. In the present study, all participants completed 8 titrating delay-discounting tasks: $100 gain, $500 gain, $500 loss, alcohol, entertainment, food, a temporary health gain, and a temporary cure from a disease. Non-tobacco users discounted most outcomes less than tobacco users overall; however, there were no differences in discounting among the different types of tobacco users. These results suggest that nicotine consumption of any kind is associated with a higher degree of impulsivity compared to non-tobacco users. Adoption of tobacco products that have been perceived as less harmful (e.g., e-cigarettes) is not associated with a baseline difference or decrease in delay discounting if adopted after a history of cigarette use.